Cocaine use and overdose mortality in the United States: Evidence from two national data sources, 2002–2018. (1st September 2020) - Cano, Manuel; Oh, Sehun; Salas-Wright, Christopher P.; Vaughn, Michael G.
Highlights: Prevalence of past-year cocaine use has increased modestly, while cocaine-involved overdose mortality has risen dramatically. In 2018, prevalence of past-year cocaine use did not significantly differ between NH Blacks and NH Whites. In 2018, cocaine-involved overdose mortality rates were more than twice as high among NH Blacks as NH Whites. NH Blacks accounted for 11.37% of the adults reporting cocaine use, yet 27.04% of the cocaine-involved overdose deaths. Abstract: Background: Cocaine-involved overdose mortality has recently risen in the United States (US), yet it is unclear to what extent patterns in cocaine-involved overdose mortality parallel patterns in cocaine use. This study: examined time trends (2002–2018) in past-year cocaine use and cocaine-involved overdose mortality in the US; and compared demographics and drug involvement of adults who reported past-year cocaine use versus adults who died of a cocaine-involved overdose. Methods: Data from two sources were utilized: (1) the National Survey on Drug Use and Health ( n = 1, 334 adults self-reporting cocaine use in 2018); and (2) the Multiple Cause of Death dataset of the National Center for Health Statistics ( N = 14, 630 adults who died of a cocaine-involved overdose in 2018). The study examined prevalence of past-year cocaine use, mortality rates for cocaine-involved overdose, 2002–2018 trends, demographic characteristics, and involvement of other drugs. Results: Results of Joinpoint Regression indicated that the prevalence of past-year cocaine use increased after 2011, with an annual percent change of 5.13, while age-adjusted cocaine-involved overdose mortality rates escalated after 2012, with an annual percent change of 26.54. In 2018, prevalence of past-year cocaine use did not significantly differ ( p = 0.09) by racial/ethnic group, yet Non-Hispanic Blacks had an age-adjusted cocaine-involved overdose mortality rate more than double the rate in Non-Hispanic Whites and significantly higher ( p < 0.001) than in any other group. Conclusions: While the prevalence of cocaine use has increased modestly, cocaine-involved overdose mortality has risen dramatically. Cocaine-involved overdose mortality is disproportionately affecting individuals who are Black, older, or with lower educational attainment.